Genetic structure of the reef grouper Epinephelus merra in the West Indian Ocean appears congruent with biogeographic and oceanographic boundaries. (20th May 2014) - Muths, Delphine; Tessier, Emmanuel; Bourjea, Jerome
Abstract The reef fauna connectivity of the West Indian Ocean (WIO) is one of the least studied globally. Here we use genetic analyses of the grouper Epinephelus merra (Bloch 1793) to determine patterns of connectivity and to identify barriers to dispersal in this WIO marine area. Phylogeographic and population‐level analyses were conducted on cytochrome b sequences and microsatellites (13 loci) from 557 individuals sampled in 15 localities distributed across the West Indian Ocean. Additional samples from the Pacific Ocean were used to benchmark the WIO population structure. The high level of divergence revealed between Indian and Pacific localities (of about 4.5% in sequences) might be the signature of the major tectonic and climatic changes operating at the Plio‐Pleistocene transition, congruently with numerous examples of Indo‐Pacific speciation. In comparison, the E. merra sequences from the Indian Ocean constitute a monophyletic clade with a low average genetic distance (d < 0.5%). However both genetic markers indicated some structure within this ocean. The main structure revealed was the isolation of the Maldives from the WIO localities (a different group signature identified by clustering analysis, great values of differentiation). Both marker types reveal further significant structure within the WIO, mainly the isolation of the Mascarene Islands (significant AMOVA and isolation‐by‐distance patterns) and some patchy structure between the northernmost localities and within the Mozambique Channel. The WIO genetic structure of E. merra appeared congruent with main biogeographic boundaries and oceanographic currents.